Electro-corrosive state diagnostics of internal surfaces of reinforced concrete supports of contact network - A. A. Kuznetsov; A. V. Ponomarev; A. G. Zverev; G. V. Volchanin (Омский научный вестник)
The article discusses a device for diagnosing the electrocorrosive state of hollow reinforced concrete supports of the contact network and power lines. The operation of the device is based on the use of a visual method for monitoring electro-corrosive defects. A design of a video endoscope is proposed that provides an improvement in image quality by eliminating fluctuations in the position of a flexible optical probe during its vertical movement, an increase in the level of automation of the diagnostic process with registration of the coordinates of defects and documentary evidence in the form of a replenished database of images of the diagnostic object — the inner surface of hollow reinforced concrete supports from the surface soil to their base.